Molecular studies on HSV: replication rate, infection capacity and progeny - Azevedo, Aleksandra (2017)
Introduction: In the last years genital herpes has emerged as one of the most prevalent sexually transmitted infections. Herpes simplex virus (HSV) is the most common cause of genital ulcer disease, with infections caused by both sub-types HSV-1 and HSV-2. A better understanding of the virus replication cycle is relevant to the pathogenesis of human diseases and is essential for the development of antiviral chemotherapy. Objectives: We aimed to shed some light on the HSV-1 and HSV-2 infectious cycle, namely their capacity of infection, replication rate and progeny, in three distinct cell lines (Vero, Vero E6 and HeLa229). We also aimed to evaluate whether the concentration of virus has any influence on the degree of the infection. Methodology: Preliminary assays were performed in order to understand which cellular concentration, viral load, nutrients’ availability and inoculation modus operandi (centrifugation versus agitation) best mimic the HSV infection. Confluent cell monolayers were infected with two HSV-2 and two HSV-1 at MOIs of 1:10, 1:1, 10:1 and 100:1. Inoculations were performed in parallel in two 24-well plates, one for quantitative real-time PCR (kPCR) and one for immunofluorescence assays, which were incubated for 30 hours at 37ºC and 5% CO2. At different times-points of infection (6, 12, 18, 24 and 30 hours p.i.), the wells were scratched for kPCR and the slides were stained with monoclonal antibodies. For kPCR assays, appropriate standard curves were generated by serial diluting plasmids cloned with HSV-1 and HSV-2 single copy genes. Results and Conclusions: Preliminary assays showed that, regardless of the viral load, it takes approximately 23 hours for the virus to complete the infectious cycle taking into account that no replication is observed after this time point. Considering the comparison between the two inoculation procedures (centrifugation versus agitation), we only observed relevant differences for lower viral loads, with centrifugation yielding more viral progeny. More specific data regarding both the HSV-1 and HSV-2 replication capacity for different MOIs are currently under evaluation.